Avaliação do metabolismo energético in vitro de formas epimastigotas de trypanossoma cruzi pré e pós tratamento específico com benzonidazol - Nogueira, Kamilla Soares (2015)
The Chagas disease is a zoonosis of huge worldwide impact that has such as vector triatomine insects belonging to the hemiptera order and such as etiological agent Trypanosoma cruzi a flagellate that presents different evolutive manners. The evolutive manners of Trypanosoma cruzi can gain energy from various sources, for example glucose and amino acids. This capacity in gain energy from various sources lead to understand how this parasite can be able to adapt and survive in different environment, be it on the vector insects or on the vertebrate host. The aim of this work was evaluate the energetic metabolism in vitro of epimastigote forms of Trypanosoma cruzi pre and post-treatment with different concentrations of benznidazole. The parasites were grown in means of Liver infusion triptose - LIT and the organic acids referring to them energetic metabolism were measured for 3º, 6º, 9º e 12º days of growing. For evaluation of the drug effect on the parasite's metabolism was added in the growing medium the following concentrations: 100 μmolar, 50 μmolar, 25 μmolar, 12.5 μmolar e 6.25 μmolar. It was possible to detect organic acids referring to glycolytic path, oxidation of fatty acids, urea cycle and citric acid of parasites in every analyzed day. It was possible to observe that the largest concentrations of drug (25, 50 e 100μmolar) induced anaerobic way of energy production. This way before the non-detection of glicossomais and mitochondrias final products, it can conclude that one of the mechanisms of action of this drug is to prevent the aerobic metabolism of the parasite, inhibiting mitochondria paths and glicossomais.